El rol del estado ecuatoriano frente a la problemática del trabajo infantil y su incidencia en la educación en la parroquia Nuevo Santa Rosa del cantón Santa Rosa y propuesta de intervención desde la perspectiva de la teoría humanista del trabajo social. - Reyes Valdiviezo, Jenny Edith (2012)
The situation of Santarerian households, like the rest of the country, is surrounded by the poverty and extreme poverty in which a considerable number of families are involved. This means that children and adolescents in many cases have to abandon their studies to work and thus help the livelihood of the home, some become small street vendors selling tails in glasses, bread, at fairgrounds and Others are looking for jobs in fishing, carpentry and in the banana plantations. In recent times, the central government has taken action in the matter, regulating this activity, such is the case that the Labor Code prohibits the access of children and adolescents to banana work and dangerous and harmful work that threaten With its good development and personal integrity, there are even sanctions for any employer who uses child labor in their work. The National and Local Government has implemented projects that provide assistance to families by providing some type of scholarship or economic stimulus in order to eradicate Child Labor and thus help parents to give the study to their children.